Portable instrument based on color sensor chip for on-site rapid detection of dissolved sulfides in environmental water samples - Gao, Ge; Qi, Ji; Fu, Longwen; Zhao, Rongfang; Zhang, Zhiyang; Chen, Lingxin (Journal of hazardous materials, 2023)
To ensure real-time validity of the detection of unstable toxic environmental pollutants, such as dissolved sulfides, we developed a portable on-site rapid analysis instrument. Through novel design of the color sensor chip-based core sensing components and the conversion between color signal and absorbance by Lambert's law, the instrument showed great performance for rapid (within 3 min) and sensitive on-site detection of sulfides in the environment. It is easy to achieve user-friendly, sample in-answer out, one-stop operation due to the touch-screen-integrated user interface of the instrument's data terminal. The detection limit of this method is 2.24 μg/L, the linear operation range is 0–1000 μg/L, and the coefficient of determination is 0.999. This instrument has been successfully applied to the on-site determination of sulfides in the Yellow River Delta and the Yantai Guangdang River in China. The portable instrument showed excellent anti-interference, good stability, and simple operation, which showed great prospects for the on-site rapid analysis of unstable targets in the environment. [Display omitted] •The portable instrument for on-site rapid detection of sulfide was developed.•The instrument based on color sensor chip was first designed and applied.•The conversion between color and absorbance was proposed by Lambert's law.•The detection limit of 2.24 μg/L for detection of sulfide.